Avaliações e sentimentos no ensino de inglês como língua adicional - Pizzol, Carla Adriana Zanatta Dal (Universidade do Vale do Rio dos Sinos, 2018)
Assessment practices are present in students’ daily lives, but little is spoken or researched about the effects that they have on learner’s feelings and how the results they achieve influence their motivation to keep learning. The purpose of this study is to highlight the perceptions of English students as an additional language about the assessment practices to which they are submitted in their learning context. It seeks to understand what feelings students experience regarding such practices and their results. Besides that, it seeks to investigate whether the way they feel influence their motivation as a language student. In order to develop this study, semi-structured interviews were carried out with seven students of English as an additional language from a language school in the metropolitan region of Porto Alegre/RS. The interviews, recorded in audio and submitted to qualitative analysis (RYAN; BERNARD, 2000), reveal positive and negative feeling regarding evaluation. Among the positive feelings are the high self-esteem, confidence and security about their language development. Among the negative feelings are the frustration, anxiety and nervousness. The results point to the need for reflection about the feelings triggered by the assessment practices in the context of teaching and learning English as an additional language.
Keywords: Inglês como língua adicional; Sentimentos; Avaliação; Entrevistas; Análise qualitativa; English as an additional language; Feelings; Assessment; Interviews; Qualitative analysis